Investigation of pharmacokinetic drug interaction between clesacostat and DGAT2 inhibitor ervogastat in healthy adult participants - Aarti Sawant‐Basak; Arthur J. Bergman; Jessica Mancuso; Sakambari Tripathy; James R. Gosset; Laure Mendes da Costa; William P. Esler; Roberto A. Calle (Wiley, 2024)
Abstract Co‐administration of clesacostat (acetyl‐CoA carboxylase inhibitor, PF‐05221304) and ervogastat (diacylglycerol O‐acyltransferase inhibitor, PF‐06865571) in laboratory models improved non‐alcoholic fatty liver disease (NAFLD)/non‐alcoholic steatohepatitis (NASH) end points and mitigated clesacostat‐induced elevations in circulating triglycerides. Clesacostat is cleared via organic anion‐transporting polypeptide‐mediated hepatic uptake and cytochrome P450 family 3A (CYP3A); in vitro clesacostat is identified as a potential CYP3A time‐dependent inactivator. In vitro ervogastat is identified as a substrate and potential inducer of CYP3A. Prior to longer‐term efficacy trials in participants with NAFLD, safety and pharmacokinetics (PK) were evaluated in a phase I, non‐randomized, open‐label, fixed‐sequence trial in healthy participants. In Cohort 1, participants (n = 7) received clesacostat 15 mg twice daily (b.i.d.) alone (Days 1-7) and co‐administered with ervogastat 300 mg b.i.d. (Days 8-14). Mean systemic clesacostat exposures, when co‐administered with ervogastat, decreased by 12% and 19%, based on maximum plasma drug concentration and area under the plasma drug concentration-time curve during the dosing interval, respectively. In Cohort 2, participants (n = 9) received ervogastat 300 mg b.i.d. alone (Days 1-7) and co‐administered with clesacostat 15 mg b.i.d. (Days 8-14). There were no meaningful differences in systemic ervogastat exposures when administered alone or with clesacostat. Clesacostat 15 mg b.i.d. and ervogastat 300 mg b.i.d. co‐administration was overall safe and well tolerated in healthy participants. Cumulative safety and no clinically meaningful PK drug interactions observed in this study supported co‐administration of these two novel agents in additional studies exploring efficacy and safety in the management of NAFLD.